2018
DOI: 10.1021/acs.analchem.7b04861
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Exosome Isolation and Protein Analysis by an Integrated Nanomaterial-Based Platform

Abstract: Exosomes play important roles in mediating intercellular communication and regulating a variety of biological processes, but clear understanding of their functions and biogenesis has not been achieved, due to the high technical difficulties involved in analysis of small vesicular structures that contain a high proportion of membrane structures. Herein, we designed a novel approach to integrate two nanomaterials carrying varied surface properties, the hydrophilic, macroporous graphene foam (GF) and the amphiphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 59 publications
2
54
0
Order By: Relevance
“…[103]). Such methods include tangential flow filtration and variations thereon [21,[104][105][106][107][108][109][110], field-flow fractionation (FFF) [111], asymmetric flow field-flow fractionation (AFFF, A4F, or AF4) [112][113][114], field-free viscoelastic flow [115], alternating current electrophoretics [116,117], acoustics [118], variations on size exclusion chromatography (SEC) [100,[119][120][121], ion exchange chromatography [122][123][124], microfiltration [125], fluorescenceactivated sorting [126,127] (especially for larger EVs including large apoptotic bodies [128] and large oncosomes [129]), deterministic lateral displacement (DLD) arrays [130], novel immunoisolation or other affinity isolation technologies [131][132][133][134][135][136][137][138], including lipid affinity [139], novel precipitation/combination techniques [140][141][142], hydrostatic filtration dialysis [143], ...…”
Section: Ev Separation and Concentration: How Misev2014 Evolves In 2018mentioning
confidence: 99%
“…[103]). Such methods include tangential flow filtration and variations thereon [21,[104][105][106][107][108][109][110], field-flow fractionation (FFF) [111], asymmetric flow field-flow fractionation (AFFF, A4F, or AF4) [112][113][114], field-free viscoelastic flow [115], alternating current electrophoretics [116,117], acoustics [118], variations on size exclusion chromatography (SEC) [100,[119][120][121], ion exchange chromatography [122][123][124], microfiltration [125], fluorescenceactivated sorting [126,127] (especially for larger EVs including large apoptotic bodies [128] and large oncosomes [129]), deterministic lateral displacement (DLD) arrays [130], novel immunoisolation or other affinity isolation technologies [131][132][133][134][135][136][137][138], including lipid affinity [139], novel precipitation/combination techniques [140][141][142], hydrostatic filtration dialysis [143], ...…”
Section: Ev Separation and Concentration: How Misev2014 Evolves In 2018mentioning
confidence: 99%
“…Currently, antibodies have been combined with some new functional nanomaterials and a series of new immunoaffinity isolation techniques have been developed. Apart from magnetic and latex beads, the most commonly used immobilization tools for antibody coating [84] include [78] highly porous monolithic silica microtips [85], graphene foam [86], superparamagnetic nanoparticles [87] and temperature-responsive magnetic nanoparticle [88] to isolate exosomes. It is reported that IAC is the most effective method, and this study shows that the specific marker in exosome isolated by IAC is more than 2-fold higher than that of UC and gradient centrifugation [89].…”
Section: Immune Affinity Capture (Iac)mentioning
confidence: 99%
“…Freeze drying formulations are one of the most reliable methodologies for highly unstable molecules like proteins, nucleic acids, etc. This enhances their practicality by increasing shelf life, lowering storage demands, reducing costs by curtailing cold chain maintenance during transportation [82,83]. However, clumping of exosomes and degradation of their cargo might be a problem during the freezedrying process.…”
Section: Challenges With Exosomes Therapeuticsmentioning
confidence: 99%